The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s00204-019-02563-x
|View full text |Cite
|
Sign up to set email alerts
|

Integrating physiologically based kinetic (PBK) and Monte Carlo modelling to predict inter-individual and inter-ethnic variation in bioactivation and liver toxicity of lasiocarpine

Abstract: The aim of the present study was to predict the effect of inter-individual and inter-ethnic human kinetic variation on the sensitivity towards acute liver toxicity of lasiocarpine in the Chinese and the Caucasian population, and to derive chemical specific adjustment factors (CSAFs) by integrating variation in the in vitro kinetic constants Vmax and Km, physiologically based kinetic (PBK) modelling and Monte Carlo simulation. CSAFs were derived covering the 90th and 99th percentile of the population distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…[36] This implies that interindividual differences are not reflected. To account for interindividual variability in AFB1 kinetics, combining the PBK modeling with Monte Carlo analysis as recently done by Ning et al to predict interindividual variation in bioactivation and liver toxicity of lasiocarpine [71] could be considered in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…[36] This implies that interindividual differences are not reflected. To account for interindividual variability in AFB1 kinetics, combining the PBK modeling with Monte Carlo analysis as recently done by Ning et al to predict interindividual variation in bioactivation and liver toxicity of lasiocarpine [71] could be considered in a future study.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent benchmark dose (BMD) modeling can be applied on the predicted in vivo dose-response data, enabling definition of a point of departure (PoD) for risk assessment, such as a BMDL x (the lower confidence limit of the benchmark dose causing an x% effect above background level) and BMDUx (the upper confidence limit of the benchmark dose causing an x% effect above background level). PBK modelling has recently been applied to describe the kinetics of three PAs, including riddelliine, lasiocarpine and monocrotaline [20,[26][27][28][29]. ▶ Fig.…”
Section: Physiologically-based Kinetic (Pbk) Modellingmentioning
confidence: 99%
“…Distinguishing between interindividual and ethnic variation is important in oncology research, especially in testing drug response and pharmacokinetic studies. [81][82][83][84][85] Examining biomarker expression in larger cohorts of patients, or using meta-analyses, can help reduce the risk of this confounding effect. 81,86 As one study concluded, thousands of samples are required to accurately contribute gene lists for predicting outcome in cancer.…”
Section: Distinguishing Interindividual From Ethnic Variability In Pdmentioning
confidence: 99%
“…89 Attempts through computational analyses and algorithms have been made to address the role of interindividual variation in population studies. 84,[86][87][88] We propose that these analyses must be applied in studies examining ethnic variation in TNBC. Given the limitation of TNBC PDX models that represent ethnic patients, more established models are required to draw accurate conclusions with respect to ethnic variation in TNBC.…”
Section: Distinguishing Interindividual From Ethnic Variability In Pdmentioning
confidence: 99%